Novel Heterogeneous Catalysts for Advanced Oxidation Processes (AOPs) - Soares, Olívia Salomé G.P; Orge, Carla; Rocha, Raquel Pinto (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
With the increasing global usage of water and the continuous addition of contaminants to water sources, new challenges have arisen that are associated with the abatement of organic pollutants, particularly those that are refractory to conventional water and wastewater treatment technologies. Advanced oxidation processes (AOPs) present a competitive alternative to promote the oxidation of organic contaminants by strong oxidative radicals generated from oxygen, ozone, wet peroxide, and UV radiation. The use of catalysts not only improves efficiency but may present remarkable cost advantages for practical applications of AOPs in the abatement of several pollutants. In this Special Issue of Catalysts, we invite authors to submit original research papers focused on the synthesis and characterization of novel heterogeneous catalysts and their uses in advanced oxidation processes for the removal of organic pollutants from aqueous solutions.